2017
DOI: 10.5935/1980-6906/psicologia.v18n3p54-65
|View full text |Cite
|
Sign up to set email alerts
|

Questionário sobre violência intrafamiliar: confiabilidade de um instrumento sobre crenças

Abstract: Resumo: O presente estudo visa analisar a confiabilidade do "Questionário sobre Crenças a Respeito da Violência Intrafamiliar". Participaram 41 estudantes de medicina e de enfermagem de uma universidade no interior de São Paulo e 39 profissionais autônomos. Testes de confiabilidade apresentaram alpha de Cronbach adequado (0,868), com resultados mais elevados retirando as questões com baixa correlação (0,894) indicando boa mensuração das crenças pelo instrumento. O teste Anova indicou que as respostas estavam r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…At the start of the research, an instrument that would be used to evaluate the conceptions of health professionals about the VACT theme was not found. Thus, to verify the effectiveness of the intervention, a questionnaire adapted from Ferrari et al 17 was used. After the alterations and, because this instrument has not been validated in the Brazilian context, the items were submitted to judges, that is, researchers with known experience in the field in which the research is included.…”
Section: Instrumentmentioning
confidence: 99%
“…At the start of the research, an instrument that would be used to evaluate the conceptions of health professionals about the VACT theme was not found. Thus, to verify the effectiveness of the intervention, a questionnaire adapted from Ferrari et al 17 was used. After the alterations and, because this instrument has not been validated in the Brazilian context, the items were submitted to judges, that is, researchers with known experience in the field in which the research is included.…”
Section: Instrumentmentioning
confidence: 99%
“…Professionals and laypersons from the United States and Brazil showed similar low scores regarding knowledge of child sexual abuse and forensic interviews (Pelisoli et al, 2015). Research within Brazil has shown that professionals in numerous fields have low levels of knowledge regarding family violence, with police officers scoring lower than professionals in education and healthcare (Ferrari et al, 2016;Leal et al, 2022). Scientifically-supported, reliable, and easy-to-access information regarding child abuse could help close this knowledge gap.…”
Section: Introductionmentioning
confidence: 99%
“…Com isso, há uma grande dificuldade ao comparar os resultados desses países com o Brasil, para além das diferenças culturais. As diferenças entre os instrumentos afetam os resultados e, com a generalização dos dados comprometida, a maior parte dos instrumentos internacionais não está validada para a população brasileira (Avery-Leaf et al, 1997;Ferrari et al, 2016).…”
unclassified